1999
DOI: 10.1007/s002109900059
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of three structurally distinct Ca2+ channel activators with single L-type Ca2+ channels

Abstract: The dihydropyridine S(-)-Bay K 8644 (Bay K), the benzoylpyrrole FPL 64176 (FPL) and the benzodiazocine CGP 48506 (CGP) are structurally unrelated L-type Ca2+ channels agonists. The aim of our study was to investigate whether these three drugs interact with different binding sites and thereby modulate the behaviour of L-type Ca2+ channels in a qualitatively different manner. Single-channel recordings were performed on CHO cells stably expressing the alpha1C-b subunit of the L-type Ca2+ channel. Mean open time a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 9 publications
2
14
0
Order By: Relevance
“…As with Ca v 1.2a, non-transfected cells and cells cotransfected only with pcDNA3.1, ␣ 2 ␦-subunits, and GFP displayed a quite sparse pattern of activity of Ca v 1.2b (Fig. 5), similar to our previous observations (26).…”
Section: Figsupporting
confidence: 89%
“…As with Ca v 1.2a, non-transfected cells and cells cotransfected only with pcDNA3.1, ␣ 2 ␦-subunits, and GFP displayed a quite sparse pattern of activity of Ca v 1.2b (Fig. 5), similar to our previous observations (26).…”
Section: Figsupporting
confidence: 89%
“…FPL did not affect [ 3 H]PN 200-110 binding; thus DHPs and FPL are thought to bind to different sites on the channel protein (16,23). However, electrophysiological evidence showed that singlechannel open probability (P o ) for a BAYK-FPL mixture exhibited a lower P o than either alone (11). This result was interpreted to suggest that although these agents bind to different sites on the Ca 2ϩ channel, a functional or physical interaction does in fact exist between them.…”
Section: ϩmentioning
confidence: 99%
“…FPL is structurally unrelated to DHPs and is thought to bind to a separate site from DHPs on the I Ca,L in a noncompetitive manner (1,4,15,16,23). However, several reports (11,15,22) suggest that there is an allosteric interaction between the binding sites for FPL and DHPs even if they do not share a common receptor on the channel protein itself. Thus there is already evidence for interactions between binding sites in I Ca,L for the two classes of agonist.…”
Section: Mechanisms Of Ryr2 Channel Activation By Fplmentioning
confidence: 99%
“…Gating mode 2 can be induced by L-type VDCC activators, stimulation of ␤-ARs (Yue et al, 1990), and through association of L-type channels with CaMKII (calcium/ calmodulin-dependent protein kinase II) (Dzhura et al, 2000). Whereas L-type VDCC activators cause more Ca 2ϩ influx as a result of a shift to mode 2 (Hess et al, 1984;Lauven et al, 1999), L-type channel blockers typically cause a stabilization of mode 0 (Hess et al, 1984).…”
Section: Contribution Of L-type Vdccs To Bap-evoked Spine Camentioning
confidence: 99%